Authigenic Iron Sulfides Indicate Sea‐Level Change on the Continental Shelf: An Illustration From the East China Sea. Issue 3 (2nd March 2021) - Liu, Jianxing; Shi, Xuefa; Liu, Qingsong; Liu, Shengfa; Liu, Yan; Zhang, Qiang; Yu, Xiaoxiao; Fang, Xisheng; Wu, Yonghua; Xu, Taoyu; Li, Jinhua
Abstract: Although sea‐level is the primary control over sedimentary architectures on continental shelves, deciphering such changes is still challenging, except for the easily recognized transgression‐regression cycles. This problem becomes more prominent in sedimentary units with relatively homogenous and fine‐grained lithologies that have been deposited over short periods. Here, we focus on a dominantly clayey silt section of a sediment core from the outer shelf of the East China Sea. Detailed rock magnetic and electron microscopy analyses indicate that authigenic greigite (Fe3 S4 ) is the major magnetic component in an almost 4‐m‐thick interval that was deposited during the late Marine Isotope Stage (MIS) 3, while pyrite (FeS2 ) is enriched in the underlying middle MIS 3 sediments. According to microfossil analyses, the identified greigite formed in a prodelta setting that was affected by cold coastal currents after the middle MIS 3, when the Taiwan Warm Current and its associated upwelling were prevailing within a middle‐outer shelf setting favorable for pyrite formation. Large‐amplitude regression occurred subsequently during the MIS 2, limiting sulfate supply and favoring the greigite preservation. Our results, along with the previous studies, demonstrate that both the material and environmental conditions that are crucial to iron sulfide survival have been largely controlled by sea‐level change. Moreover, we make a preliminary proposition that a water depth range of 30–60 m is more likely to lead to the enrichment of greigite on continental shelves. We, therefore, provide a promising avenue for the assessment of sea‐level change on continental shelves over orbital and even suborbital timescales. Key Points: Greigite was identified as the major magnetic mineral in almost 4‐m‐thick late MIS 3 sediments from the outer shelf of the East China Sea Authigenic greigite and pyrite have great potential to indicate sea‐level change on continental shelves even on suborbital timescales Water depths of 30–60 m are likely to be more suitable for extensive formation and preservation of greigite in continental shelf sediments